BREAST CANCER SURVIVAL AFTER SURGERY AND OTHER TREATMENTS: A LITERATURE REVIEW - Ramadhanti , Ismaya; Izzati , Mutiara Nur; Fitri , Asti Elysia Rahmatul; Rahmayanti , Verina Lutfiah; Hamid , Endah Nurhalimah; Hanifah , Laily (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2025)
Background: Breast cancer treatment has changed over the years, both surgically and medically. Purpose: This study aims to conduct a literature review on survival in breast cancer patients after undergoing surgery and other treatments. Methods: A literature review was conducted from the databases PubMed, ScienceDirect, and Google Scholar using the keywords